Rasch Analysis of Household Waste Reduction Behavior: Case Study in Sunten Jaya, Bandung Barat Regency - Rohima, Ira Endah; Hasbiah, Astri Widiastuti (Journal of Community Based Environmental Engineering and Management, 2023)
The reduction of domestic waste in developing countries is a critical issue that requires attention. Behavioural intentions of households can lead to reduce, reuse and recycle behaviour in waste management. Many factors influence the reduction of waste. Psychological and behavioural characteristics often hinder the effectiveness of technical solutions in managing household waste, so it is important to understand human behaviour to design effective policies. Rural areas also face waste problems, but they do not receive as much attention as urban areas. This research aims to identify the behavioural intentions of households to reduce waste in a small village in Bandung Barat Regency. This study uses Rasch model to measure a person’s perspective in an objective way. Data for this study was collected using a questionnaire. The questions were rated on a five-point Likert scale. The number of respondents who participated in this study was 27. The small number of respondents was due to difficulties in finding respondents, as most people were farming at the time of the study. The result shows that the person’s reliability is statistically misfit, whereas the item reliability is fit. The respondent/person misfit may be because the respondents are farmers with a low level of education. The Cronbach’s alpha value, which measures the interdependence between the person and the item, is 0.70. Since the item reliability is 0.95 and the person reliability is 0.62, it can be concluded that the quality of the items of the instrument is good, and the consistency of the respondents’ answers is also good. Questionnaire item I8 is the most difficult question for respondents to agree with a value of +2.09 logit. On the other hand, the easiest questionnaire item to agree on is I18 with -1.74 logit. From the results it can be concluded that the respondents know about waste separation. However, they never carried out waste separation. It can be inferred that the behaviour of the respondents does not reflect their knowledge.